Association of Topical Corticosteroids With Reduced Vulvar Squamous Cell Carcinoma Recurrence in Patients With Vulvar Lichen Sclerosus - Chin, Simone (JAMA Dermatol, 2020)
This cohort study uses data from a medical record review of a dermatogynecology practice to describe the association between reduced recurrence of vulvar squamous cell carcinoma and use of topical corticosteroids in the treatment of vulvar lichen sclerosus.